2009
DOI: 10.1111/j.1540-8175.2008.00851.x
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Outflow Tract Gradient Provoked by Upright Position or Exercise in Treated Patients with Hypertrophic Cardiomyopathy without Obstruction at Rest

Abstract: In nonobstructive HCM patients under treatment, the LVOT gradient was inducible by upright position in 21.6% and by upright moderate exercise in 34.5%. The minimal septal-mitral distance may be useful to identify patients with provocable obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
2
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 23 publications
0
59
2
3
Order By: Relevance
“…Several studies have reported the importance of upright positioning during exercise in the detection of provocable (latent) or labile left ventricular (LV) outflow tract gradients in hypertrophic cardiomyopathy [3][4][5][6][7][8][9][10][11][12]. Also, passive orthostatic tests (without exercise) are helpful in diagnostic evaluation in other diseases predisposing to LV outflow tract gradients [8,12].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported the importance of upright positioning during exercise in the detection of provocable (latent) or labile left ventricular (LV) outflow tract gradients in hypertrophic cardiomyopathy [3][4][5][6][7][8][9][10][11][12]. Also, passive orthostatic tests (without exercise) are helpful in diagnostic evaluation in other diseases predisposing to LV outflow tract gradients [8,12].…”
Section: Introductionmentioning
confidence: 99%
“…This type of obstruction is highly dynamic and varies in different physiological situations. Often not observed in resting conditions, it can be elicited during passive standing or exercise in an upright position, and sometimes during the Valsalva manoeuvre [42]. In this situation, drag forces deriving from high-velocity, abnormally directed anterograde systolic flow within the LV produce a systolic anterior motion.…”
Section: Hypertrophic Cardiomyopathymentioning
confidence: 99%
“…In a series of patients submitted to percutaneous alcohol septal ablation, but, even though its application is arguable for recording purposes 41 , the Valsalva maneuver and the exercise were found to produce similar degrees of elevation of the gradient in outflow tract 42 . In another series, the obstruction was triggered by the standing position in 21.6% of the cases and by moderate exercise in 34.5% 43 .…”
Section: Echocardiogrammentioning
confidence: 99%